Selectivity and Specificity of Sphingosine-1-Phosphate Receptor Ligands: Caveats and Critical Thinking in Characterizing Receptor-Mediated Effects - Waeber, Christian; Salomone, Salvatore (Frontiers in Pharmacology, 2011)
Receptors for sphingosine-1-phosphate (S1P) have been identified only recently. Their medicinal chemistry is therefore still in its infancy, and few selective agonists or antagonists are available. Furthermore, the selectivity of S1P receptor agonists or antagonists is not well established. JTE-013 and BML-241 (also known as CAY10444), used extensively as specific S1P2 and S1P3 receptors antagonists respectively, are cases in point. When analyzing S1P-induced vasoconstriction in mouse basilar artery, we observed that JTE-013 inhibited not only the effect of S1P, but also the effect of U46619, endothelin-1 or high KCl; JTE-013 strongly inhibited responses to S1P in S1P2 receptor knockout mice. Similarly, BML-241 has been shown to inhibit increases in intracellular Ca2+ concentration via P2 receptor or α1A-adrenoceptor stimulation and α1A-adrenoceptor-mediated contraction of rat mesenteric artery, while it did not affect S1P3-mediated decrease of forskolin-induced cyclic AMP accumulation. Another putative S1P1/3 receptor antagonist, VPC23019, does not inhibit S1P3-mediated vasoconstriction. With these examples in mind, we discuss caveats about relying on available pharmacological tools to characterize receptor subtypes.